On Divine Simplicity and Perfect Being Theology - Huneeus Alliende, Clemente (New blackfriars, 2025)
This paper relates the metatheological approach known as ‘Perfect Being Theology’ (PBT) and criticisms of the doctrine of divine simplicity (DDS) in its Thomistic version. After briefly contrasting PBT with Thomas Aquinas’ alternative approach, which will be labeled ‘Analogical Natural Theology’ (ANT), it is shown that an option for the first approach dominates much of what has been written on simplicity. Then the structure of ANT is outlined in an attempt to explain the stronger commitment this project has toward DDS.